The influence of anchoring group position in ruthenium dye molecule on performance of dye-sensitized solar cells. (March 2018) - Zalas, Maciej; Gierczyk, Błażej; Bossi, Alberto; Mussini, Patrizia Romana; Klein, Maciej; Pankiewicz, Radosław; Makowska-Janusik, Małgorzata; Popenda, Łukasz; Stampor, Waldemar
Abstract: The effect of anchoring group position and, in consequence, the orientation of the ruthenium dye molecule on titania surface on the performance of dye-sensitized solar cells has been studied intensively. Three model ruthenium sensitizing dyes bearing carboxylic anchoring group in ortho, meta or para position were synthesized and well characterized by spectroscopic, electrochemical, photophysical and photochemical measurements. The results were confronted with the quantum-mechanical calculations and discussed. The para derivative has been found as the most effective sensitizer with the cells efficiency twice higher than the meta and four times higher than the ortho derivatives. Highlights: The effect of anchoring group position in dye molecule on DSSC performance have been investigated. Three model dyes have been synthesized and characterized. Para position of the anchor has been found as the most efficient one. Our findings are of importance for further development of new sensitizers.